Perempuan Sebagai Anak dan Hak-Haknya dalam Perkawinan (Studi terhadap Peraturan Perundang-undangan dan Praktek di Pengadilan Agama) - Fatima Fatima (JURNAL INDO-ISLAMIKA, 2012)
This paper aims to investigate how women or girls as daughters are administered in Islamic family laws and how they are awarded rights in regard to marriage. It also analyses how judges at Islamic courts solve the cases involving women as daughters. It, therefore, discusses how, according to Indonesian Islamic family law, women, as daughter could obtain permissions to get married when their parents are reluctant to marry them. It also discusses how they have also right to obtain permission to get married although they have not reached the minimum age of marriage. Investigating a number of judgments from Islamic courts of Central, South, West and East Jakarta and using socio-legal approach, this paper reveals that the proposal for marriage dispensation by parents at religious courts increased from year to year and that the proposals were often approved by judges. It also demonstrates that judges mostly conclude that the reluctance of parents to marry their daughters is based on legal reasons so that judges often decide to appoint ‘wali hakim’, as a substitute to ‘wali nasab’.